Boosting Public Service Organizational Performance in Indonesia: An Integrated PLS-SEM and NCA Study of SAMSAT Offices - Ferdy Ferdy; Patrick Marcos Lech Walesa Nababan; Nikasia Novita Cintarso; Romy Pramono; Indri Maya Sari; Halek Mu'min (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines whether transformational leadership and service innovation improve public service performance directly and indirectly through organizational ambidexterity in SAMSAT offices delivering vehicle registration and taxation services under the Samsat Digital Nasional program, addressing contradictory evidence on leadership's effect on public performance. Design/methodology/approach – Data from 120 SAMSAT officials, supervisors, and staff in Batam and Tanjung Pinang were analyzed using PLS-SEM combined with Necessary Condition Analysis (NCA) in SmartPLS 4, drawing on Transformational Leadership, Service Innovation, Organizational Ambidexterity, and Dynamic Capability Theory. Findings/Results – All five direct paths were significant, and ambidexterity partially mediated both the leadership-performance and innovation-performance links (VAF = 27.5% and 34.5%). The model explained 38.1% of performance variance with acceptable fit (SRMR = 0.060) and medium predictive relevance (Q²predict = 0.268), while necessity analysis showed ambidexterity and service innovation, but not leadership, to be necessary conditions for performance. Originality/Value – The findings are consistent with organizational ambidexterity acting as one plausible mechanism behind mixed leadership-performance evidence in the public-sector literature, rather than a definitive resolution of that inconsistency, since only one organizational context and one cross-sectional dataset are analyzed here; within this sample, ambidexterity and service innovation, but not leadership, met the threshold for a necessary condition. The main implication is that SAMSAT management should treat leadership development, innovation investment, and ambidextrous capability-building as complementary priorities, phased according to organizational feasibility, rather than assuming leadership alone is sufficient or that statistical importance translates directly into implementation priority.